KESADARAN PEDAGANG DAN MASYARAKAT DALAM MENJAGA KEBERSIHAN LINGKUNGAN DI SEKITAR PASAR SURANTIH KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - -, Rifo - (STKIP PGRI Sumbar, 2014)
This study aimed to obtain in-depth data on traders and public awareness in keeping the environment around the District Silk Surantih Market Regency South Coast. This research is qualitative, this research informants were ommunity leaders, merchants and the people who live around the Market Surantih. Data collection techniques used in this study is the observation, interview and documentation, data collection tools that the researchers themselves with their own plunge actively spaciousness. Analysis techniques used are data reduction, decision-making and Verification. Based on the findings in the field and interview the results of this study are as follows: Knowledge, understanding and community merchants are not in accordance with their behavior, they interpret a clean environment from waste but in fact do not, still the amount of garbage that littered the market Surantih, Takingpart in merchants and the community in keeping the environment around Surantih market can be seen from the attitude and behavior, respectively, where the community is also partly responsible for keeping the environment in which Surantih market by providing garbage disposal sacks and cardboard in landfills and temporary they also pay a levy to guard as much as USD 2000 Market Behavior Surantih community in applying discipline in keeping the environment clean is by way partisifasi and mutual cooperation.